Dark tourism spectrum: Visual expression of dark experience. (December 2022) - Lv, Xingyang; Luo, Haohan; Xu, Shuangyu; Sun, Jiaojiao; Lu, Ruihua; Hu, Yubei
Abstract: Dark-light spectrum was used to express the depth of dark experience in dark tourism. Based on embodied cognition theory, this paper examined the visual expression of tourists' dark tourism experience. Five consecutive studies were conducted including analysis of tourists' photos in online reviews of 53 dark tourism destinations worldwide, charcoal pencil painting tasks of selected dark tourism sites in lab experiments, and field experiment. Results showed that tourists with darker experience tend to use deeper visual darkness to express their feelings, in the forms of painting and photographs, even when the cognitive process (i.e., expression in the form of words) is omitted. This psychological mechanism explains the scientific principle behind dark tourism spectrum. Our research suggests a new way of interpretation of tourist image data (e.g., photos) and sheds light for effective management of tourist experience.